Microfluidic isolation and release of live disseminated breast tumor cells in bone marrow - Minh-Chau N. Le; Dongjiang Chen; Kierstin A. Smith; David D. Tran; Z. Hugh Fan (PLoS ONE, 2025)
Breast cancer represents a significant therapeutic challenge due to its aggressive nature and resistance to treatment. A major cause of treatment failure in breast cancer is the presence of rare, low-proliferative disseminated tumor cells (DTCs) in distant organs including the bone marrow. This study introduced a microfluidic-based approach to improve the immunodetection and isolation of these rare DTCs for downstream analysis, with an emphasis on optimizing immunocapture, release, and enrichment methods of live DTCs as compared to the standard approach for blood-borne circulating tumor cells (CTCs). EGFR (epidermal growth factor receptor) and EpCAM (epithelial cell adhesion molecule), two key cell surface markers in breast cancer, were validated as efficient cell capture targets for DTCs within microfluidic chambers. Furthermore, we demonstrated that a combination of 0.25% trypsin and impulse was the most effective for releasing captured cells, maintaining high viability, and preserving essential cellular characteristics. Using a metastatic mouse breast cancer model, we achieved a 47.9-fold enrichment of live DTCs. Analysis of blood and bone marrow samples obtained from a breast cancer patient with minimal residual disease at two timepoints revealed a reduction in CTCs and an increase in DTCs following adjuvant chemotherapy. This observation suggested a potential dynamic interplay between CTCs and DTCs in response to therapy. Our results underscore the potential of the microfluidic approach in enhancing DTC detection and shed light on the importance of monitoring both CTCs and DTCs in breast cancer prognosis and treatment response assessment.